The Effect of Product Design, Green Product, and Product Review on Interest in Buying Electric Motorbikes in the Special Region of Yogyakarta - Suparmanto, Suparmanto; Gunawan, Hamzah (PT FORMOSA CENDEKIA GLOBAL, 2025)
Motorcycles are a simple and popular mode of transportation in many countries, including Indonesia. Motorbikes can be ridden by two to three passengers with cargo as well. This study aims to analyze the effect of Product Design, Green Product, and Product Review on Interest in Buying Electric Motorbikes in the Special Region of Yogyakarta. The population in this study were people in Yogyakarta, with a research sample of 100 respondents. The data collection technique used a questionnaire. The data analysis technique uses multiple regression analysis, partial t hypothesis testing using the SPSS 30 program: (1) Product Design has a significant effect on buying interest in electric motorbikes, (2) Green Product has a significant effect on buying interest in electric motorbikes, (3) Product Review has a significant effect on buying interest in electric motorbikes.